2007
DOI: 10.1007/s10327-007-0032-x
|View full text |Cite
|
Sign up to set email alerts
|

Fruit rot of Strawberry pear (pitaya) caused by Bipolaris cactivora

Abstract: Strawberry pear (pitahaya, pitaya) [Hylocereus undatus (Haw.) Britt. and Rose] postharvest fruit rot was found at an agricultural products store in Itoman city, Okinawa Prefecture in 2006. The symptoms included depressed, water-soaked lesions with olive to black powdery spots coalescing into a soft rot. The causal fungus was identified as Bipolaris cactivora (Petrak) Alcorn. This is the first report of strawberry pear fruit rot caused by B. cactivora.Keywords Pitaya Á Fruit rot Á Bipolaris cactivora Á Water-so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Fungal species and genera such as Alternaria, Bipolaris ( Taba et al, 2007 ), Stomiopeltis ( Ajitomi et al, 2017 ), Nigrospora ( Alam et al, 2017 , 2020 ), Passalora (i.e., Passalora fulva, syn. Cladosporium fulvum) ( Altin, 2016 ), Stagonospora, Ascochyta ( Milgroom and Peever, 2003 ), Diaporthe, Gibberella ( Guenther and Trail, 2005 ), Mycosphaerella, Zasmidium, Sterigmatomyces, Helicoma, Puccinia, Exobasidium, Lasiodiplodia, Exserohilum, Curvularia ( Oeurn et al, 2015 ; Hafiz et al, 2019 ), Phytophthora, Peniophora ( Taylor, 1969 ), and Neofusicoccum ( Hara et al, 2016 ) are commonly associated with plant disease and are most likely opportunists, which develop on stressed or dying fruit and leaf tissues ( Om et al, 1999 ; Galsurker et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fungal species and genera such as Alternaria, Bipolaris ( Taba et al, 2007 ), Stomiopeltis ( Ajitomi et al, 2017 ), Nigrospora ( Alam et al, 2017 , 2020 ), Passalora (i.e., Passalora fulva, syn. Cladosporium fulvum) ( Altin, 2016 ), Stagonospora, Ascochyta ( Milgroom and Peever, 2003 ), Diaporthe, Gibberella ( Guenther and Trail, 2005 ), Mycosphaerella, Zasmidium, Sterigmatomyces, Helicoma, Puccinia, Exobasidium, Lasiodiplodia, Exserohilum, Curvularia ( Oeurn et al, 2015 ; Hafiz et al, 2019 ), Phytophthora, Peniophora ( Taylor, 1969 ), and Neofusicoccum ( Hara et al, 2016 ) are commonly associated with plant disease and are most likely opportunists, which develop on stressed or dying fruit and leaf tissues ( Om et al, 1999 ; Galsurker et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diseased fruits may be rejected during export due to the biosecurity rules of the importing countries. The common fungal pathogens that attack dragon fruits are Bipolaris cactivora (Taba et al 2007, Tarnowski et al 2010 and N. dimidiatum (Lan et al 2012, Ezra et al 2013, Yi et al 2015, but no fruit disease has yet been scientifically reported in the Philippines. Fruit diseases are better addressed when the cause of the disease is identified.…”
Section: Introductionmentioning
confidence: 99%
“…Pitaya can be easily cultivated in the open air and remains relatively disease‐free. However, recently, successive disease outbreaks such as mosaic (Natsuaki & Shinkai, 2001), anthracnose (Taba et al, 2003), Rhizopus rot (Taba et al, 2006), fruit rot (Taba et al, 2007), and Gilbertella stem rot (Taba et al, 2011) have been reported. In particular, stem rot is a considerable problem, which not only causes softening and rotting of the stem nodules but also causes poor fruiting and postharvest damage.…”
Section: Introductionmentioning
confidence: 99%